Lignin Biodegradation with Laccase-Mediator Systems - Christopher, Lew Paul; Yao, Bin; Ji, Yun (Frontiers in Energy Research, 2014)
Lignin has a significant and largely unrealized potential as a source for the sustainable production of fuels and bulk high-value chemicals. It can replace fossil-based oil as a renewable feedstock that would bring about socio-economic and environmental benefits in our transition to a biobased economy. The efficient utilization of lignin however requires its depolymerization to low-molecular weight phenolics and aromatics that can then serve as the building blocks for chemical syntheses of high-value products. The ability of laccase to attack and degrade lignin in conjunction with laccase mediators is currently viewed as one of the potential “breakthrough” applications for lignin valorization. Here, we review the recent progress in lignin biodegradation with laccase-mediator systems, and research needs that need to be addressed in this field.